Marauders by gerry duggan, volume 2 ebook - Duggan, Gerry (Marauders (2019), 2020)
Collects Marauders (2019) #7-12. A life on the ocean waves! As Verendi's plans against Krakoa grow, Captain Kate Pryde and her seafaring Marauders find themselves missing something vital — and it's about to cause Storm and Emma Frost to come to blows! Meanwhile, a very small attack on the new mutant nation is quickly growing into something much bigger thanks to the size-changing Yellowjacket! Can the crew swat him before his sting succeeds? To prevail, the Marauders must set their sights on the power-dampening technology that seems to have made its way into far too many human hands — most notably, the Russian Army. The Hellfire Trading Company's wrath will be swift and harsh! But tragedy is about to strike — and soon, all of Krakoa will be reeling from an unthinkable, and perhaps insurmountable, death!